Answer:
The equation of the graph that is represented is:
[tex]y=-3x[/tex]
Step-by-step explanation:
We know that the equation of a line passing through two points (a,b) and (c,d) is calculated by the using the two-point formula:
[tex]y-b=\dfrac{d-b}{c-a}\times (x-a)[/tex]
From the graph we observe that the line passes through (-4,12) and (0,0)
[tex]y-12=\dfrac{0-12}{0-(-4)}\times (x-(-4))\\\\i.e.\\\\y-12=\dfrac{-12}{0+4}\times (x+4)\\\\i.e.\\\\y-12=\dfrac{-12}{4}\times (x+4)\\\\i.e.\\\\y-12=-3(x+4)\\\\i.e.\\\\y-12=-3x-12\\\\i.e.\\\\y=-3x[/tex]
Hence, the equation of line is:
[tex]y=-3x[/tex]